If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 38 + -2x = 14 + -10x Solving 38 + -2x = 14 + -10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '10x' to each side of the equation. 38 + -2x + 10x = 14 + -10x + 10x Combine like terms: -2x + 10x = 8x 38 + 8x = 14 + -10x + 10x Combine like terms: -10x + 10x = 0 38 + 8x = 14 + 0 38 + 8x = 14 Add '-38' to each side of the equation. 38 + -38 + 8x = 14 + -38 Combine like terms: 38 + -38 = 0 0 + 8x = 14 + -38 8x = 14 + -38 Combine like terms: 14 + -38 = -24 8x = -24 Divide each side by '8'. x = -3 Simplifying x = -3
| 25=7-9x | | 9x-7=4x+23 | | 3x+13=-11-3x | | 5a+a^2=0 | | 3p+6p=3 | | 3+2n=2 | | 3/7*7/3= | | 3m^2+12m-15=0 | | 20=y-5 | | 24-6q= | | 3.4x-3.3=5.1-22.2x | | -3y-7(y+4)=-y+6-3y | | 0=5x^4-150x^2 | | x+3x-26=18 | | 9x-1=50-8x | | 11+9x=43 | | 14x+43-25x=128 | | -7y=x | | 3+65x=52x+12 | | (6x^2-5x+12)+(9x^2+7x-68)= | | 4/7=-12/x | | x-40/x=14 | | 30x=-25-9x^2 | | 6(2x-5)-4=2 | | 2x+6y=2x+3y | | 10-2x=x-10 | | x-40/x=0 | | 3x=-2x+23 | | 2x+6y=2x+6y | | 1/x= | | 3+91x=39x+39 | | -2(7+x)=3(1-2x) |